Hukum Perlindungan Konsumen dan Transaksi Pre-Order Produk UMKM di Era Ekonomi Digital - Marthen Arnoldus Rehabeam Manongga; Cecep Suhardiman (Pusat Riset dan Inovasi Nasional, 2026)
The rapid development of e-commerce has significantly increased the participation of Micro, Small, and Medium Enterprises (MSMEs) in the digital economy, particularly through the use of pre-order transaction schemes. Although Indonesia has established a relatively comprehensive legal framework for consumer protection and electronic transactions, pre-order transactions involving MSME products remain highly vulnerable to fraud. This study aims to analyze the effectiveness of legal regulation and implementation of consumer protection in pre-order transactions conducted through e-commerce platforms, to identify legal, institutional, and social factors contributing to consumer vulnerability, and to examine the role of the state and e-commerce platform providers in strengthening consumer protection as a public policy. This research employs a normative legal research method with a prescriptive-analytical character, utilizing statutory, conceptual, and case approaches. The findings reveal that existing consumer protection mechanisms remain partial and predominantly reactive, as they do not specifically accommodate the inherent risks of pre-order transactions nor are they supported by preventive supervision and enforcement mechanisms. Consumer vulnerability arises from the interaction between regulatory gaps, institutional limitations, and social conditions such as information asymmetry and low legal and digital literacy. Accordingly, this study emphasizes the necessity of a synergistic role between the state and e-commerce platforms in developing and implementing consumer protection policies oriented toward substantive justice and fraud prevention in the digital economy.